Indonesia’s Struggle with Education Inequality: Is Reform the Answer? - Sidauruk, Johan Manik; Susilowati, Monica; Akbar, Kamal Karimullah (Universitas Negeri Semarang, 2025)
This study examines the persistent issue of educational inequality in Indonesia and explores whether educational reforms can effectively address the disparities within the country’s educational system. Despite substantial investments in education and ongoing efforts to enhance access, significant gaps remain in the quality of education between urban and rural areas, as well as among different socio-economic groups. The research analyzes the primary factors contributing to educational inequality, including regional disparities, resource allocation, teacher quality, and the accessibility of educational infrastructure. Findings reveal that while recent reforms, such as the School Operational Assistance (BOS) program and the expansion of vocational education, have made some strides in reducing inequality, significant challenges persist in ensuring equal opportunities for all students. The study highlights that systemic issues, such as the uneven distribution of resources and inadequate teacher training, continue to undermine educational equity. The novelty of this research lies in its comprehensive examination of both policy interventions and the broader socio-economic factors that perpetuate educational inequality. Given the profound implications of educational inequality on Indonesia’s long-term social and economic development, this research is of particular urgency. The study contributes to the wider discourse on educational reform by offering concrete recommendations for advancing educational equity, including improving resource allocation, strengthening teacher training, and ensuring that reforms are more effectively tailored to the needs of marginalized communities.